Board Characteristics and Firm Performance : Malaysia’s Government-Linked Companies (GLCS) Compliance to Green Book - Noraisyah, Abd Rahman; Mohd Waliuddin, Mohd Razali (Human Resource Management Academic Research Society (HRMARS), 2019)
The Government-Linked Companies Transformation (GLCT) Programme was introduced in 2005 as the Malaysia Government efforts to improve the performance of government-linked companies (GLCs) under its control. One of the main policy thrusts in this framework is the need to upgrade the effectiveness of GLCs boards which led to the launching of the Green Book on April 2006. Focusing on the Green Book structuring high-performing board guidelines, this study tries to examine whether compliance to its recommended board characteristics of size, independence and remuneration has any effect on GLCs performance. Thus, GLCs financial performance for three years before (2004, 2005 and 2006) and three years after (2007, 2008 and 2009) the guidelines became mandatory effective on 1 January 2007 are analyzed and compared. The results show that the Green Book is a successful tool to increase board effectiveness in its monitoring function. However, compliance to board characteristics of size, independence and remuneration do not affect GLCs performance. Thus, it can be concluded that the influence of the Green Book as corporate governance factor is insufficient to explain the variations in GLCs performance.